Risk of metabolic syndrome in postmenopausal breast cancer survivors - Buttros, Daniel de Araújo Brito [UNESP]; Nahás, Eliana Aguiar Petri [UNESP]; Vespoli, Heloísa Maria de Luca [UNESP]; Uemura, Gilberto [UNESP]; De Almeida, Bruno Da Rosa [UNESP]; Nahas-Neto, Jorge [UNESP] (Wolters Kluwer, 2013)
The aim of this study was to assess the risk of metabolic syndrome (MetS) in postmenopausal breast cancer survivors as compared with postmenopausal women without breast cancer. METHODS: In this cross-sectional study, 104 postmenopausal breast cancer survivors were compared with 208 postmenopausal women (controls) attending a university hospital. Eligibility criteria included the following: amenorrhea longer than 12 months and aged 45 years or older, treated for breast cancer, and metastasis-free for at least 5 years. The control group consisted of women with amenorrhea longer than 12 months and aged 45 years or older and without breast cancer, matched by age and menopause status (in a proportion of 1:2 as sample calculation). Clinical and anthropometric data were collected. Biochemical parameters, including total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, glucose, and C-reactive protein, were measured. Women showing three or more diagnostic criteria were diagnosed as having MetS: waist circumference of 88 cm or larger, blood pressure of 130/85 mm Hg or higher, triglycerides level of 150 mg/dL or higher, high-density lipoprotein cholesterol level lower than 50 mg/dL, and glucose level of 100 mg/dL or higher. For statistical analysis, Student's t test, χ2 test, and logistic regression (odds ratio [OR]) were used. RESULTS: The mean (SD) age of breast cancer survivors was 60.6 (8.6) years, with a mean (SD) follow-up of 9.4 (4.4) years. A higher percentage of breast cancer survivors (46.2%) were obese as compared with controls (32.7%; P < 0.05), and a smaller percentage showed optimal values for low-density lipoprotein cholesterol, glucose, and C-reactive protein versus controls (P < 0.05). MetS was diagnosed in 50% of breast cancer survivors and in 37.5% of control group women (P < 0.05). Among the MetS diagnostic criteria, the most prevalent was abdominal obesity (waist circumference >88 cm), affecting 62.5% and 67.8% of the participants, respectively. In the control group, breast cancer survivors had a higher risk for MetS (OR, 1.66; 95% CI, 1.04-2.68), dysglycemia (OR, 1.05; 95% CI, 1.09-3.03), and hypertension (OR, 1.71; 95% CI, 1.02-2.89). CONCLUSIONS: Postmenopausal breast cancer survivors present a higher risk of developing MetS as compared with women without breast cancer. © 2012 by The North American Menopause Society.
Keywords: Breast cancer survivors; Menopause; Metabolic syndrome; Risk factors; C reactive protein; cholesterol; estrogen receptor; glucose; high density lipoprotein cholesterol; low density lipoprotein cholesterol; progesterone receptor; triacylglycerol; abdominal obesity; adult; amenorrhea; arterial pressure; axillary lymph node; blood pressure; body mass; breast cancer; cancer chemotherapy; cancer hormone therapy; cancer radiotherapy; cancer size; cancer survivor; cardiometabolic risk; cholesterol blood level; conservative treatment; controlled study; cross-sectional study; disease duration; disease severity; exercise; female; follow up; glucose blood level; hormone substitution; human; hypertension; major clinical study; mastectomy; metabolic syndrome X; parity; postmenopause; protein blood level; risk assessment; triacylglycerol blood level; waist circumference